Pengembangan Aplikasi Pengelolaan Arsip Digital Berbasis Phprad di PT Istana Kebon Jeruk - Windi Lestari; Roni Faslah; Rizki Firdausi Rachmadania (Politeknik Kampar, 2025)
This study aims to develop and evaluate the feasibility of a digital archive management application built using PHPRad at PT Istana Kebon Jeruk. The research employs a Research and Development (R&D) design utilizing the ADDIE development model. The unit of analysis focuses on the company’s archival management processes, with research subjects consisting of administrative and sales division employees as end-users, and media experts serving as validators of application quality. Data were collected through observations and questionnaires. The final output of this study is an application equipped with key features including sales database management, archive disposal, and the administration of incoming and outgoing correspondence. The feasibility assessment resulted in a “Highly Feasible” category, and user testing conducted with employees likewise yielded a “Highly Feasible” category. Therefore, the PHPRad-based digital archive application is deemed highly feasible and practical for digital archive input and management. During the development process, several challenges were encountered. These constraints were successfully addressed by providing user training, developing a comprehensive user manual, and implementing basic security mechanisms through login-based access control. The findings of this study are expected to support the sustainable implementation of this application as part of PT Istana Kebon Jeruk’s digital transformation in archival management.